(untitled) (Research, Society and Development, 2021)
There is an increase in imports of mineral fertilizers to supply the needs of the domestic market. Thus, organomineral fertilizers appear as an alternative for supplying nutrients to plants and reducing dependence on imports of mineral fertilizers. The experiment was structured in a randomized block design with five treatments and four replications, the treatment arrangement was carried out by combining the application of mineral and organomineral fertilizer in planting and cover. At 30, 60 and 90 (pasty grain phase) DAE, the variables under analysis were obtained, such as stem diameter (DC), plant height (AP) and ear insertion height (IEA). To estimate the green (MV) and dry (MS) mass of the plants, aerial parts were collected during the full flowering of the crop. There were few changes observed in the development of the plants as a result of the use of the organomineral in planting or cover, and only at 30 DAE can we observe statistical differences between the different treatments in the variables height and diameter of the plants. Corn showed higher productivity with the use of organomineral fertilizer for planting and covering.